Implementation of The Analytical Hierarchy Process (AHP) Algorithm to Support Decision Making For Determining Superior Orange Comodities Orange in Selorejo Village - Yuni Agung Nugroho; Hanifatus Sahro; Rangga Pahlevi Putra; Hasbibullah (Lumina Infinity Academy Foundation, 2026)
This study aims to explore the selection of orange varieties as the primary crop for farmers in Selorejo Village, Sengkaling, Malang Regency. Oranges have high economic value and are important for meeting the community’s nutritional needs; however, selecting the right variety must take into account factors such as cultivation expertise, environmental influences, and income potential.The research question posed is: “Which orange variety is most suitable to be the primary crop in Selorejo Village?” The study employs the Analytical Hierarchy Process (AHP), enabling a systematic analysis of criteria and alternatives. The research findings are expected to provide new insights into the selection of optimal orange varieties and to integrate environmental and economic factors that are often overlooked. Data analysis using AHP includes initial data collection, applying AHP to define criteria and alternatives, determining the priority of criteria and alternatives, and ensuring consistency in the analysis. Focusing on Selorejo Village, this study aims to make a tangible contribution to strategies for more sustainable orange cultivation and to improve farmers’ welfare. The results of the study indicate that income criteria are the primary factor in selecting orange varieties for farming in Selorejo Village, followed by cultivation practices and environmental influences, while the main orange varieties chosen are siem oranges, followed by mandarin oranges and sweet oranges.